The first local three-wheeler manufacturing initiative in Bangladesh: A scope for Runner Automobiles - Niloy, Nayeem Afzal (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.